2019
DOI: 10.20473/amnt.v3i2.2019.85-88
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Citra Tubuh dengan Status Gizi pada Siswi di SMA Negeri 9 Surabaya

Abstract: Background: Teenage age is a period of transition from childhood to adulthood. At this age there will be changes in body shape that can affect teenagers' perceptions of body image, especially adolescent girl. The result of a preliminary study at Senior High School 9 Surabaya showed that 7 out of 10 female students were dissatisfied with their body shape so they made certain efforts, such as managing their diet to exercise for get an ideal body.Objective: The purpose of this study was to analyze whether there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
2
3
0
5
Order By: Relevance
“…This shows that the respondent is in middle adolescence 19 . Similar research related to body image on adolescent girls carried out by Bimantara et al 5 , also found a similar age range between 15 to 18 years in female students of class XI at SMA Negeri 9 Surabaya. According to Piaget's theory of cognitive development 20,21 , children aged 12-15 years have entered the stage of development of formal operations which means that apart from experiencing physical changes and maturation of reproductive cells, children begin to experience social changes in the way they think and process information.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This shows that the respondent is in middle adolescence 19 . Similar research related to body image on adolescent girls carried out by Bimantara et al 5 , also found a similar age range between 15 to 18 years in female students of class XI at SMA Negeri 9 Surabaya. According to Piaget's theory of cognitive development 20,21 , children aged 12-15 years have entered the stage of development of formal operations which means that apart from experiencing physical changes and maturation of reproductive cells, children begin to experience social changes in the way they think and process information.…”
Section: Resultssupporting
confidence: 81%
“…The process of growth and development in adolescence occur rapidly, causing an increase in the need for energy and nutrients. In several previous studies which have been carried out by Deshmusk and Kulkarni 4 , and Bimantara et al 5 it has been found that there is a correlation between body image and nutritional status, especially in adolescents. If the body image is bad or commonly referred to as negative body image occurs, there will be nutritional problems 2 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…10 Hasil penellitian ini sejalan dengan penelitian sebelumnya yang menunjukan bahwa terdapat hubungan antara persepsi citra tubuh dengan status gizi. 18,25 Sementara itu, penelitian yang dilakukan oleh Ahadzadeh et al (2018) juga menunjukan bahwa BMI memiliki korelasi negatif dengan persepsi citra tubuh (β = -0,090, p <0,005). 26 Berbagai perubahan fisik yang terjadi pada remaja merupakan proses yang alamiah, yang akan dilalui oleh semua individu, namun seringkali ketidaktahuan remaja terhadap perubahan itu sendiri membuat mereka hidup dalam kegelisahan dan perasaan cemas.…”
Section: Pembahasan Hubungan Persepsi Citra Tubuh Dengan Status Gizi unclassified
“…A positive body image is when an individual is satisfied and acceptable with changes in her body shape (Jannah et al, 2019). Meanwhile, negative body image is when an individual can not accept her body shape (Bimantara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%